A novel interval arithmetic approach for solving differential-algebraic equations with VALENCIA-IVP - Rauh, Andreas; Brill, Michael; Günther, Clemens (Zielona Góra: Uniwersytet Zielonogórski)
The theoretical background and the implementation of a new interval arithmetic approach for solving sets of differential-algebraic equations (DAEs) are presented. The proposed approach computes guaranteed enclosures of all reachable states of dynamical systems described by sets of DAEs with uncertainties in both initial conditions and system parameters.
Keywords: ordinary differential equations; differential-algebraic equations; VALENCIA-IVP; verified simulation; inverse control problems